Disability, education and employment in developing countries From charity to investment - Lamichhane, Kamal (Cambridge, 2015)
The book challenges common assumptions about people with disabilities and advocates the need for an immediate paradigm shift. It is based on the premise that human capital such as education and employment are the most important factors for inclusion and economic empowerment of the disabled, and their accessibility not only improves their livelihood, but also brightens the prospects of their poor families and society as a whole